2021
DOI: 10.1093/neuonc/noab095
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol converts NF-κB into a tumor suppressor in glioblastoma with defined antioxidative properties

Abstract: Background The transcription factor NFκB drives neoplastic progression of many cancers including primary brain tumors (glioblastoma; GBM). Precise therapeutic modulation of NFκB activity can suppress central oncogenic signalling pathways in GBM, but clinically applicable compounds to achieve this goal have remained elusive. Methods In a pharmacogenomics study with a panel of transgenic glioma cells we observed that NFκB can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 41 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…on transgenic mouse brain tumor cells showed CBD-induced lack of p65 phosphorylation in Ser-311, attenuation of NF-κB signaling and ultimately promoting cancer cell death due to CBD cytotoxicity. This study suggested antagonistic activity between Nrf2 and p65 mediated by CBD [ 130 ]. It has also been shown that an attempt to apply CBD (2.5 μM) to TNFα-treated C2C12 myoblasts did not change the level of phosphorylated p65 in Ser-536 [ 123 ].…”
Section: The Role Of Cannabidiol In the Nrf2 - Nf-κb Crosstalkmentioning
confidence: 99%
“…on transgenic mouse brain tumor cells showed CBD-induced lack of p65 phosphorylation in Ser-311, attenuation of NF-κB signaling and ultimately promoting cancer cell death due to CBD cytotoxicity. This study suggested antagonistic activity between Nrf2 and p65 mediated by CBD [ 130 ]. It has also been shown that an attempt to apply CBD (2.5 μM) to TNFα-treated C2C12 myoblasts did not change the level of phosphorylated p65 in Ser-536 [ 123 ].…”
Section: The Role Of Cannabidiol In the Nrf2 - Nf-κb Crosstalkmentioning
confidence: 99%
“…Also, NF-K B is shown as molecular target in GBM, and is linked to poor prognosis. NF-K B-induced genes have been shown to be promoting cell survival and proliferation of GBM cells [44]. Therefore, we investigated the effect of avopiridol on NF-K B.…”
Section: Flavopiridol Inhibits Proliferation Colony Formation and Mig...mentioning
confidence: 99%
“…NF-κB promotes the expression of ZEB-1 in glioma, which in turn represses E-cadherin and results in anoikis resistance ( 105 ). On the other hand, inhibition of the gene transactivation function of NF-κB by cannabidiol induces cell death in GBM ( 106 ).…”
Section: Cytoplasmic Proteins and Anoikis Resistancementioning
confidence: 99%